Expeditious synthesis of SnO2 nanoparticles through controlled hydrolysis and condensation of Tin alkoxide in reverse microemulsion. Issue 5 (1st April 2017) - Wang, Jiasheng; Wu, Wenpei; Wang, Wan-Hui; Bao, Ming
Abstract: SnO2 is a very important material in many areas such as catalysis, gas sensors, and lithium ion batteries. In this study, we successfully prepared SnO2 nanoparticles from tin (IV) isopropoxide in reverse microemulsion, which is still a big challenge up to now due to the uncontrollable hydrolysis and condensation rate. The hydrolysis and condensation process was slowed down by diffusion limitation, i.e., increasing the viscosity of the reaction media by introducing PVA-224 to the reverse microemulsion. The strategy developed here is of general directive significance for preparing other metal oxide nanoparticles in reverse microemulsion from corresponding metal alkoxide precursors who have fast hydrolysis and condensation rate.